Lifestyle‐ and comorbidity‐related factors for the prescription of proton pump inhibitors after Helicobacter pylori eradication in Japan. Issue 11 (10th November 2021) - Shimada, Furitsu; Endo, Hiroyoshi; Takamori, Ayako; Matsunaga, Takuya; Fujimoto, Shun; Shirai, Shimpei; Kakiuchi, Toshihiko; Akutagawa, Takashi; Sakata, Yasuhisa; Node, Koichi; Yamanouchi, Kohei; Nakamura, Shotaro; et al.
Abstract: Background and Aim: The aim of the present study was to examine the lifestyle‐ and comorbidity‐related determinant factors of the prescription of proton pump inhibitors (PPIs) for patients in whom Helicobacter pylori has been eradicated, and to evaluate the relationship between PPI prescription and the severity of endoscopic esophagitis. Methods: This retrospective study included patients who underwent H. pylori eradication from May 2012 to September 2016 at Saiseikai Karatsu Hospital. All patients received upper gastrointestinal endoscopy before H. pylori eradication. Patients with open peptic ulcers and/or malignant diseases were excluded, and a final total of 389 patients were evaluated. Medical records were reviewed to determine the prescription of PPIs after H. pylori eradication, lifestyle‐related factors, and comorbidities. Lifestyle‐related factors were confirmed by a questionnaire. Results: PPIs were administered to 124 of 389 patients (31.9%). The only lifestyle‐related risk factor for the prescription of PPIs after H. pylori eradication was older age ( P < 0.01). Hypertension increased the prescription of PPIs ( P = 0.034). The prescription of PPIs was not influenced by the presence of grade A esophagitis, whereas the PPI prescription rate was significantly increased in patients with grades B/C/D endoscopic esophagitis ( P < 0.01). The grade of chronic gastritis before H. pylori eradication had no effect on the prescription of PPIs. Conclusion: The lifestyle‐ and comorbidity‐related risk factors for the prescription of PPIs after H. pylori eradication were older age and hypertension, while mild endoscopic esophagitis had no influence on PPI prescription. Abstract : The lifestyle‐ and comorbidity‐related risk factors for the prescription of proton pump inhibitors after Helicobacter pylori eradication were older age and hypertension, while mild endoscopic esophagitis had no influence on proton pump inhibitor prescription.